PENGARUH KINERJA KEUANGAN TERHADAP PROFITABILITAS PADA PT. PELABUHAN INDONESIA I (PERSERO) - STIE Lhokseumawe (Sekolah Tinggi Ilmu Ekonomi Lhokseumawe, 2017)
This study aimed to examine the effect of asset growth and liquidity and simultaneouspartial effect on profitability PT. Pelabuhan Indonesia I (Persero). The analyticalmethod used in this research is multiple linear regression analysis. The results ofthis study indicate that (1) the regression coefficient value asset growth is notequal to zero, then H1 is accepted and can be interpreted that the asset growtheffect on the level of profitability Return on Assets (ROA). (2) The value of theregression coefficient of liquidity is not equal to zero, then H1 is accepted and canbe interpreted that the liquidity effect on the level of profitability Return on Assets(ROA). (3) Based on the draft terms of hypothesis testing to certify that the growthof liquidity of assets and the level of profitability Return on Assets (ROA) is theleast. Referring to these requirements, the results of the study received Ha, ith itcan be said that the growth of assets and liquidity simultaneously contributed to theincreased profitability.